AI-powered search - Grainger, Trey; Turnbull, Doug 1980-; Irwin, Max (Manning Publications, 2023)
"Modern search is more than keyword matching. Much, much more. Search that learns from user interactions, interprets intent, and takes advantage of AI tools like large language models (LLMs) can deliver highly targeted and relevant results. This book shows you how to up your search game using state-of-the-art AI algorithms, techniques and tools."--Back cover.
Includes index. - Description based on print version record
Keywords: Web search engines; Artificial intelligence; Natural language processing (Computer science); Moteurs de recherche sur Internet; Intelligence artificielle; Traitement automatique des langues naturelles; artificial intelligence